Enhancing Teacher Education Students’ Teaching Skills Through Pedagogical Communication in Teaching Simulations - Kulsum, Umi; Mulyati, Yeti; Sastromiharjo, Andoyo (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to identify and explore how pedagogical communication strategies enhance the teaching skills of teacher education students through teaching simulations. Pedagogical communication-based simulations were designed to strengthen students’ self-confidence, speaking skills, classroom management, and audience engagement. This study employed a mixed-methods approach using a sequential explanatory design, beginning with quantitative data collection through questionnaires and teaching skills tests, followed by qualitative data from semi-structured interviews and classroom observations. The findings revealed that the implementation of pedagogical communication strategies had a significant positive impact on students’ teaching skills, particularly self-confidence, which increased from a mean score of 3.4 to 4.3, along with improvements in speaking skills. Nevertheless, challenges related to audience engagement and time management remained. The novelty of this study lies in integrating pedagogical communication into teaching simulations, transforming conventional microteaching from a performance-oriented exercise into a communication-centered learning process that explicitly develops verbal, non-verbal, relational, and reflective teaching competencies. This integration provides a more comprehensive framework for preparing future teachers and offers practical implications for teacher education curricula by embedding effective communication as a core component of teaching competence.